Constructing the moral body: Self-care among older adults with multiple chronic conditions. (May 2013) - Clarke, Laura Hurd; Bennett, Erica V.
Older adults are increasingly living with and managing multiple chronic conditions. The self-management of illness occurs in a social and political context in which the responsibility for health has shifted from the State to the individual, who is expected to be an active consumer of health care. Although there has been extensive investigation of the management of single chronic conditions, the realities of living with multiple morbidities have largely been ignored, particularly among older adults. Addressing this gap, our study entailed in-depth interviews with 35 older Canadian adults, aged 73 to 91, who had between three and 14 chronic conditions. Self-care emerged as a primary means by which our participants managed their illnesses. Specifically, all of our participants were engaged in some form of self-care in order to cope with often debilitating physical symptoms and functional losses. They also utilized self-care because they had reached the limits of available medical treatment options. Finally, our participants argued that self-care was a moral responsibility that was underscored by gendered motivations. Whereas the men tended to emphasize the importance of self-care for the achievement of masculine ideals of control and invulnerability, the women suggested that self-care allowed them to maintain feminine norms of selflessness and sensitivity to the needs of others. In this way, self-care enabled the men and women to reframe their aging, chronically ill bodies as moral, socially valued bodies. We discuss our findings in relation to the extant research and theorizing pertaining to self-care, gender, and healthism.